ANALISIS POTENSI AIR TERJUN DI DESA KOTA LEKAT MUDIK, KECAMATAN HULU PALIK, KABUPATEN BENGKULU UTARA 2024 - Oktiani, Nia; Andriani , Dila; Adha , Yudha Dian; Febriadha , Reni Dwi; Amanda , Jeri (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The main work programme of the KKN group is "Analysis of the potential of waterfall tourism in the village of Lekat Mudik, Hulupalik district, North Bengkulu district". In this waterfall, there is insufficient infrastructure starting from roads and other support facilities. Therefore, the student group of KKN 115 cooperates with the local village government. The activities we are conducting are surveys and plans for the promotion of the name and development of tourism through the ideas of students to be offered to the local village exploration.